Features of human papillomavirus infection frequency in different regions of the Russian Federation (literature review) - E. V. Belyaeva; O. A. Tokarskaya; T. A. Bairova (Acta Biomedica Scientifica)
Numerous studies have shown the role of human papillomavirus (HPV) in the generation of cervical cancer. The review presents Russian researching data aboutfrequency of the HPV in different regions of the Russian Federation. The regional feature in the frequency of the HPV is observed. The average population frequency of the HPV varies from 13 to 63 % in different region. The frequency of the HPV reaches 82 % in groups of patients with dysplasia of the 3rd degree and cervical cancer. The most oncogenic type 16 the HPV is the most common virus among other papillomavirus in the most Russian regions that corresponds to the global data. This type of virus is the most common in both groups of women and men. Type 16 of HPV with high frequency is detected in different age groups, and among clinically healthy patients and in groups of patients with various gynecological pathologies. Modern methods of molecular diagnostics, in particular, the PCR method, allow to detect and genotype the HPV with high sensitivity and specificity, and to determine the viral load. The PCR method in screening programs can identify risk groups of the urogenital pathology in examined women.